Transition Skills Profile Developed in A Concerted Effort of Youth, Educators And Employers Based on Delphi Hybrid Method - Marta DOBRZYNIAK (Communications of International Proceedings, 2022)
The paper refers to successful management of transitions in the whole life span. The framework of transition skills and the process of supporting them is the focal issue of the research. The motive of the research presented in the paper is the framework of skills that are of importance for successful transition from education to work. It also refers to a scope of collaborative ways of supporting the development of these skills. The literature refers mostly to either future skills or career management skills whereas transition skills are rarely addressed. The most significant void though is that there is no reference in the literature to tripartite process of identifying and developing transition skills that includes youth’s input in a collaborative, concerted effort with participation of educators and employers. The researcher applied the Hybrid Delphi methodology that integrated focus group interviews, nominal groups, and Delphi techniques. The methodology of the research consisted of three Delphi rounds that took place in three locations with the participation of youth, employers and educators – all playing the roles of experts. The most important findings of the research covered the identification of transition skills accompanied by the ways of supporting these skills. The final list of 111 skills lead to identification of 5 categories and 20 subcategories. A separate finding is the list of methods that are perceived supportive for the development of the above skills and are recommended to be agreed upon and applied by both educators and employers.
Keywords: Employability; Skills; Transition; Youth Work; Support.